Molecular Docking of Bicycloproline Derivative Synthetic Compounds on Envelope Protein: Anti-SARS-CoV-2 Drug Discovery - Syaiful Prayogi; Binar Asrining Dhiani; Asmiyenti Djaliasrin Djalil (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Although a SARS-CoV-2 vaccine is readily available, new cases of COVID-19 are still occurring. New drug discovery is needed to treat COVID-19. Protein E is one of the potential targets. Two synthetic compounds of bicycloproline derivatives have the potential to be developed. Objective: This study aimed to estimate the interaction of bicycloproline compounds to protein E in-silico. Methods: There were two bicycloproline-derived compounds, MI-09 and MI-30, used in docking. Remdesivir was used as a reference ligand. The crystal structure of the E protein was created using homology modeling, while the test compound was drawn using the Marvin Sketch. MOE 2022.02 and BDS 2021 were used for docking and visualization processes. Results: The pentamer of the SARS-CoV-2 E protein obtained a clash score (1.06); poor rotatomer (0.00%); favored rotamers (98.11%); Ramachandran favored (96.43%); Ramachandran outlier (1.78%); Rama Z-score (-1.08); and mol probity (1.04). Research shows promising inhibition potential of the MI-09 and MI-30. The MI-30 has the best binding energy of -10.3326 kcal/mol. Conclusion: The docking results show that MI-30 has potency as an inhibitor of protein E and can be developed in treating COVID-19. Further research is needed to confirm the result by in vitro and in vivo studies.